Silicon heterojunction solar cells toward higher fill factor. (16th January 2020) - Martini, Luca; Serenelli, Luca; Menchini, Francesca; Izzi, Massimo; Tucci, Mario
Abstract: One of the most limiting factors in the record conversion efficiency of amorphous/crystalline silicon heterojunction solar cells is the not impressive fill factor value. In this work, with the aid of a numerical model, the ways to enhance the cell fill factor up to 85% are investigated in detail, considering the properties of conventional amorphous‐doped films, wider Energy gap layers, and transparent conductive oxide films. The band alignment among the various materials composing the heterojunction is the key to high efficiency but becomes an issue for the solar cell fill factor, if not well addressed. One of the most interesting outcomes of this work is the evidence of hidden barriers arising between the transparent conductive oxide and both selective contacts, due to the mismatch between their work functions. The measurement of light current‐voltage characteristics performed at low temperature is proposed as a way to identify the presence of these barriers in efficient solar cells that do not possess high fill factor values. Experimental J‐V characteristics compared with numerical simulations demonstrated that the sometimes neglected cell base contact needs instead a more careful consideration. To this aim, a model to predict the presence of a hidden barrier at the base contact that limits the cell fill factor is proposed. Abstract : The paper illustrates, with the aid of simulations, the limiting factors for achieving Fill Factors (FFs) up to 85% in heterojunction solar cells. A possible hidden barrier has been identified in the n‐type c‐Si based heterojunctions, depending on the workfunction of the transparent conductive oxide applied on the base contact, not easy to be recognized at room temperature, but able to limit the achievable FF. An experimental method to verify the barrier presence is provided, together with a model confirmed by simulations.